Dopamine in the auditory brainstem and midbrain: co-localization with amino acid neurotransmitters and gene expression following cochlear trauma - Fyk-Kolodziej, Bozena E.; Shimano, Takashi; Gafoor, Dana; Mirza, Najab; Griffith, Ronald D.; Gong, Tzy-Wen; Holt, Avril Genene (Frontiers in Neuroanatomy, 2015)
Dopamine (DA) modulates the effects of amino acid neurotransmitters, including GABA and glutamate, in motor, visual, olfactory and reward systems (Hnasko et al., 2010; Stuber et al., 2010; Hnasko and Edwards, 2012). The results suggest that DA may play a similar modulatory role in the auditory pathways. Previous studies have shown that deafness results in decreased GABA release, changes in excitatory neurotransmitter levels, and increased spontaneous neuronal activity within brainstem regions related to auditory function. Modulation of the expression and localization of tyrosine hydroxylase (TH; the rate limiting enzyme in the production of DA) in the IC following cochlear trauma has been previously reported (Tong et al., 2005). In the current study the possibility of co-localization of TH with amino acid neurotransmitters (AANs) was examined. Changes in the gene expression of TH were compared with changes in the gene expression of markers for AANs in the cochlear nucleus (CN) and IC to determine whether those deafness related changes occur concurrently. The results indicate that bilateral cochlear ablation significantly reduced TH gene expression in the CN after two months while in the IC the reduction in TH was observed at both three days and two months following ablation. Furthermore, in the CN, glycine transporter 2 (GlyT2) and the GABA transporter (GABAtp) were also significantly reduced only after two months. However, in the IC, DA receptor 1 (DRDA1), vesicular glutamate transporters 2 and 3 (vGluT2, vGluT3), GABAtp and GAD67 were reduced in expression both at the three day and two month time points. A close relationship between the distribution of TH and several of the AANs was determined in both the CN and the IC. In addition, GlyT2 and vGluT3 each co-localized with TH within IC somata and dendrites. Therefore, the results of the current study suggest that DA is spatially well positioned to influence the effects of AANs on auditory neurons.